DIVERSIFIKASI ENERGI BATUBARA MENJADI BAHAN BAKAR CAIR DITINJAU DARI TEMPERATUR DAN WAKTU PENCAIRAN TERHADAP JUMLAH MINYAK YANG DIHASILKAN - Lestari, Sutini Puji (Politeknik Negeri Sriwijaya, 2018)
Energy needs in Indonesia continue to increase from year to year, especially fossil energy. This condition encourages the government to be more creative in managing and utilizing the available energy sources more wisely. Coal is one of the main energy in Indonesia which in its utilization can be a promising alternative energy by being converted to liquid form. The liquefaction process of coal is influenced by various factors of operating conditions. Operating conditions are an important part that affects the process and results of coal liquefaction conversion. The operating conditions consist of temperature, time, and pressure. In coal liquefaction research there are several variables that can be taken, among others, fixed and variable non-fixed. The fixed variable is the ratio of mixture of raw materials and solvent. While the variable is not fixed in the form of time of melting and melting temperature. From the research results obtained the highest oil acquisition at a temperature of 400oC with a melting time of 120 minutes that is equal to 66.72%. the physical properties of the product such as density and spgr approach gasoline but the flash point is still too high that is between 75-78oC